Pelatihan Desain dan Kemasan Produk Sebagai Upaya Meningkatkan Omset UMKM di Kota Batam - Debby Arisandi; Ahmad Fitriansyah (Lembaga Kajian Demokrasi dan Pemberdayaan Masyarakat (LKD-PM), 2021)
The Micro, Small, and Medium Enterprises (MSMEs) sector contributed 60.34% to the gross domestic product (GDP) and assisted the absorption of labor by 97.22%. The problem is, there are still many MSMEs that are not aware or do not understand that good and attractive product packaging will bring added value to the products it offers. As a result, some products that actually have high selling value/quality do not sell in the market. This activity aims to increase the understanding of MSME players of the importance of packaging so that the products offered an increase in added value and can differentiate packaging based on function, type, and material. The implementation of community service activities was carried out on 18-19 July 2017 in the Gurindam Building Hall of the Batam City Education Office. The activity was carried out in collaboration with the Dinas Koperasi dan Usaha Mikro Kota Batam, which was attended by 128 MSMEs. The results of the activity were in the form of new packaging for participant products that were more attractive, informative, and modern.